Sistem Pendukung Keputusan Diklat Tenaga Kerja Sarjana Terbaik Menerapkan Metode OCRA - Agustina Sidabutar; Mesran, Mesran; Mesran, Rian Syahputra (Journal of Decision Support System Research, 2024)
Manpower is a very important part in supporting the success of a company. In planning the needs of a company, the workforce is the most important part in conducting the training program in determining the workforce that meets the company's qualifications. Of course, in supporting the success of a company, it can be seen from the quality of work of the workforce. In the training for the best undergraduate workers, obstacles or problems sometimes arise that cause difficulties during the training for the best undergraduate workers. Decision support system (DSS) is a computer-based system that is very interactive, which helps in making a decision to utilize data and models in solving unstructured and semi-structured problems. This research was conducted using the Operational Competitiveness Rating Analysis (OCRA) method. Where this method is able to analyze in various sectors and compare from several different decision units. The calculation results of this method will be in accordance with expectations if the selected alternative meets the predetermined criteria. Thus a decision support system is needed in assisting decision making in determining the best undergraduate manpower training at the North Sumatra Provincial Manpower Office.